Cognitive Aspect of Dhakon Games in Painting Art Creation with Augmented Reality Technology - Arum Wilis Kartika Ayuningtari; Martinus Dwi Marianto (Gondang: Jurnal Seni dan Budaya, 2023)
This art creation was born because of the author's anxiety about the lack of child-friendly nowadays games. Games on gadgets are mostly not very child-friendly and will have a negative impact on them, so there is a need for educational games such as traditional dhakon games. This creation aims to create a work of painting that comes from one of the hidden essences of dhakon games, which can hone the cognitive aspects of children. The painting art creation uses practice-based research method. The process of collecting data is obtained through observation, literature study, and interviews. The result of this creation is a two-dimensional painting that is representational, deformative, and has symbolic meaning with acrylic on canvas media combined with AR (augmented reality) technology trough trans-media approach. This painting has the title “Gemi, Setiti, Ngastiti, Ngati-ati”. This creation is useful as a medium of criticism and as a medium of education to the public about the essence of a game has a big role in the child's growth and development process, so parents must be selective in choosing children's games. In addition, this art creation is also an attempt to revitalize the dhakon game as a product of the past culture that is full of educational values but sadly has been abandoned by many people.